Coagulopathy reversal in intracerebral haemorrhage - Wengui Yu; Alexander Jacob Sweidan; Navneet Kaur Singh; Joseph Luke Conovaloff; Matthew Bower; Leonid I Groysman; Mohammad Shafie (Stroke and Vascular Neurology, 2020)
As intracerebral hemorrahge becomes more frequent as a result of an aging population with greater comorbidities, rapid identification and reversal of precipitators becomes increasingly paramount. The aformentioned population will ever more likely be on some form of anticoagulant therapy. Understanding the mechanisms of these agents and means by which to reverse them early on is critical in managing the acute intracerebral hemorrhage.